2002
DOI: 10.1128/jvi.76.22.11329-11342.2002
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus RIDβ Subunit Contains a Tyrosine Residue That Is Critical for RID-Mediated Receptor Internalization and Inhibition of Fas- and TRAIL-Induced Apoptosis

Abstract: The adenovirus-encoded receptor internalization and degradation (RID) protein (previously named E3-10.4K/14.5K), which is composed of RID␣ and RID␤ subunits, down-regulates a number of cell surface receptors in the tumor necrosis factor (TNF) receptor superfamily, namely Fas, TRAIL receptor 1, and TRAIL receptor 2. Down-regulation of these "death" receptors protects adenovirus-infected cells from apoptosis induced by the death receptor ligands Fas ligand and TRAIL. RID also down-regulates certain tyrosine kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 81 publications
(99 reference statements)
1
28
2
Order By: Relevance
“…2B and 7). The importance of the equivalent residue (Tyr 124 ) in Ad5 14.5 was noted in a study using a heterologous overexpression system in COS7 cells aimed at identifying residues involved in signal transduction (25). The authors speculated that Tyr 124 may have a function in endocytosis although trafficking of 14.5 was not investigated.…”
Section: Three Of the Five Motifs Are Crucial For 104 -145 Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B and 7). The importance of the equivalent residue (Tyr 124 ) in Ad5 14.5 was noted in a study using a heterologous overexpression system in COS7 cells aimed at identifying residues involved in signal transduction (25). The authors speculated that Tyr 124 may have a function in endocytosis although trafficking of 14.5 was not investigated.…”
Section: Three Of the Five Motifs Are Crucial For 104 -145 Functionmentioning
confidence: 99%
“…The two 10.4 species form a disulfide-linked dimer via a conserved cysteine residue at position 31 (24) and associate non-covalently with the 14.5 protein in the ER (3). 14.5 is a type I transmembrane protein and the Ad5 product has been shown to be O-glycosylated and serine-phosphorylated (3,25). Both proteins seem to be exposed on the plasma membrane (26), but a thorough quantitative assessment is lacking.…”
mentioning
confidence: 99%
“…Ads have a rather complex infrastructure in which the viral genes produce numerous proteins that prevent the death of infected cells early after infection and other proteins that favor cell death at later stages (6,28,33,38,42,52). Several viral encoded proapoptotic and antiapoptotic proteins are known to maintain temporal control of the Ad on the host cell.…”
mentioning
confidence: 99%
“…Long considered dispensable for viral replication in vitro, more recent studies have suggested an important role for the E3 region, in vivo (Ilan et al, 1997;Yu et al, 1999a). The E3 proteins function as modulators of the immune response and, in later stages of the viral life cycle, assist in host cell lysis and spread of progeny virions (Gooding et al, 1988(Gooding et al, , 1991Krajcsi and Wold, 1992;Hermiston et al, 1993;Tollefson et al, 1996;Lichtenstein et al, 2002Lichtenstein et al, , 2004. Therefore, deletion of some or all of these genes may result in an increased immune response that could enhance destruction of the tumor mass.…”
Section: Considerations For Virus Designmentioning
confidence: 99%